Metil Paration'nun Piruvat Kinaz Enzim Aktivitesine Etkisi - Dere, Egemen; Arı, Ferda (Muş Alparslan Üniversitesi, 2021)
Methyl parathion is an organophosphate group insecticide used against pests in agriculture and general fields. Insecticides have a significant toxic effect on the environment and living organisms. Methyl parathion, which causes different toxicity in humans, is also known to affect important enzymes that control metabolism. Pyruvate kinase that allosteric properties (EC.2.7.1.40) is the last enzyme of glycolysis and provides control in glycolysis followed by molecular pathways. In our study, the effect of Methyl parathion on Pyruvate kinase enzyme activity was investigated. Methyl parathion LD50 dose (7mg.kg-1) was administered intraperitoneally to male and female rats at different periods (2, 4, 8, 16, 32, 64 and 72 hours). Pyruvate kinase enzyme activity was analyzed in liver, kidney, brain and small intestine tissues of rats. As a result of exposure of Methyl parathion, increases in Pyruvate kinase enzyme activity were generally determined in rat tissues. It was remarkable that the activations took place earlier, especially in the brain tissue. It was observed that these activations in liver, kidney and small intestine tissues were earlier in females than in males. As a result, the application of Methyl parathion was found to cause increases in pyruvate kinase enzyme activity in rat tissues. It was determined that methyl parathion affects glucose metabolism and the other metabolic pathways. Therefore, it should be considered that methyl parathion insecticide affects metabolism and may cause different health problems and precautions should be taken in use by paying attention to the application dose recommended by the World Health Organization.

Metil paration, tarımda ve genel alanlarda zararlılara karşı kullanılan organofosfat grubu bir insektisittir. İnsektisitlerin çevre ve canlı organizmalar üzerinde önemli derecede toksik etkileri bulunmaktadır. İnsanlarda farklı toksisiteye neden olan Metil paration’un metabolizmayı kontrol eden önemli enzimleri etkilediği bilinmektedir. Allosterik özellik gösteren Piruvat kinaz (EC.2.7.1.40), glikolizin son enzimidir ve glikoliz ile devamındaki moleküler yolaklarda kontrolü sağlamaktadır. Çalışmamızda Metil paration’nun Piruvat kinaz enzim aktivitesi üzerine etkisi araştırıldı. Metil paration’un LD50 dozu (7mg.kg-1) intraperitoneal olarak farklı periyotlarla (2, 4, 8, 16, 32, 64 ve 72 saat) erkek ve dişi sıçanlara uygulandı. Sıçanların karaciğer, böbrek, beyin ve ince bağırsak dokularında Piruvat kinaz enzim aktivitesi analiz edildi. Metil paration maruziyeti sonucunda sıçan dokularında genel olarak Piruvat kinaz enzim aktivitesinde artışlar belirlendi. Bu aktivasyonların özellikle beyin dokusunda daha erken saatlerde gerçekleşmiş olması dikkat çekicidir. Karaciğer, böbrek ve ince bağırsak dokularında aktivasyonların dişilerde erkeklerden daha erken saatlerde olduğu gözlendi. Sonuç olarak bir insektisit olan Metil paration uygulamasının sıçan dokularında piruvat kinaz enzim aktivitesinde artışlara neden olduğu bulundu. Metil parationun glikoz metabolizmasını ve buna bağlı olarak diğer metabolik yolakları etkilediği tartışıldı. Bu nedenle Metil paration insektisitinin metabolizmayı etkilediği, farklı sağlık sorunlarına neden olabileceği düşünülmeli ve Dünya Sağlık örgütünün önerdiği uygulama dozuna dikkat edilerek güvenli kullanım için önlemler alınmalıdır.
The Effect of Methyl Parathion on the Pyruvate Kinase Enzyme Activity
msufbd
Keywords: Insecticide; Methyl parathion; Pyruvate kinase; Piruvat kinaz; İnsektisit; Metil paration